Health-care professionals’ knowledge, attitudes and behaviours relating to patient capacity to consent to treatment: An integrative review - Lamont, Scott (Nursing ethics, 2013)
This integrative review aims to provide a synthesis of research findings of health-care professionals’ knowledge, attitudes and behaviours relating to patient capacity to consent to or refuse treatment within the general hospital setting. Search strategies included relevant health databases, hand searching of key journals, ‘snowballing’ and expert recommendations. The review identified various knowledge gaps and attitudinal dispositions of health-care professionals, which influence their behaviours and decision-making in relation to capacity to consent processes. The findings suggest that there is tension between legal, ethical and professional standards relating to the assessment of capacity and consent within health care. Legislation and policy guidance concerning capacity assessment processes are lacking, and this may contribute to inconsistencies in practice.